PENGARUH KUALITAS AUDITOR, AUDIT TENURE DAN DEBT DEFAULT TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN - Oktaviani, Oktaviani; Challen, Auliffi Ermian (Department of Accounting, Faculty of Economics & Business, 2020)
Going concern audit opinion defined as opinion state by the auditors based on their audit, concludes that substantial doubt exists with regard to the company’s ability to continue functioning as a business entity. This study aims to obtain empirical evidence about the effect of auditor quality, audit tenure, and debt default on the acceptance of going concern audit opinion. The sample used in this study is manufacturing companies listed on the Indonesia Stock Exchange and have fulfilled the criteria that existed during the 2013-2017 period, a total of 20 companies. Data analysis techniques using logistic regression. The results of this study empirically prove that auditor quality and the debt default has a positive effect on the acceptance of going concern audit opinion, audit tenure has a negative effect on the acceptance of going concern audit opinion.